Immunotherapy in cervical cancer: From the view of scientometric analysis and clinical trials - Xing, Yang; Yasinjan, Feroza; Du, Yajie; Geng, Huayue; Zhang, Ying; He, Minghua; Guo, Rui; Yang, Lei; Cui, Jiayue; Mu, Dongmei; Liu, Ziling; Wang, Hong (Frontiers in Immunology, 2023)
Background Cervical cancer is the fourth most cancer and the fourth leading cause of cancer-related deaths in women worldwide. Current treatment for patients with advanced cervical cancer is limited. And in the urgent demand for novel effective therapies both as the first and the second line treatment for these patients, immunotherapy is developing fast and has made some achievements. Methods This study incorporated 1,255 topic-related articles and reviews from 1999 to 2022 in the Web of Science Core Collection (WoSCC). The WoS platform, Citespace, and VOS viewer provided the annual distribution of publications and citations, the analysis of researching countries and institutions, references, keywords (co-occurrence analysis, burst analysis, and timeline view analysis), and researching authors, respectively. For clinical trials, 720 trials and 114 trials from ClinicalTrials.gov and ICTRP were retrieved, respectively. And 296 trials were finally incorporated into the analysis. Results The scientometric analysis showed that the study of immunotherapies in cervical cancer developed fast in recent years. Most publications were from the United States, followed by China. Seven of the top 10 co-cited references belong to clinical trials, and five of them were published in recent five years. There are lots of clinical trials us specific treatment patterns, some of which have represented excellent effects. Conclusions Both the scientometric analysis of the 1,255 publications and the analysis of clinical trials showed that the field of immunotherapies in cervical cancer developed so fast in recent years. It was found that a lot of clinical trials using various immunotherapies (mainly vaccine therapy, adoptive cell therapy, immune checkpoint blockade, and antibody-drug conjugate) for advanced cervical cancer are currently ongoing or have represented considerable effect. Centered in immunotherapies, immune checkpoint blockades have represented great efficacy and huge potential, especially combined with other therapies such as chemotherapy, targeted therapy, and other immunotherapies.